METODE BAYES DALAM EVALUASI KINERJA PENYULUH PERTANIAN - Dewi Suranti; Hari Aspriyono (Jurnal Informatika, 2020)
Performance is a very important factor in determining success in assessing work quality. Good performance is the hope of all parties in an institution, including agricultural institutions. The Sukaraja Agricultural Extension Service Technical Unit (UPT BPP) always supports to improve the performance of extension workers in order to improve the quality of extension workers. Evaluation of broadcasting performance is carried out from the beginning of the activities carried out, starting from the preparation, implementation, evaluation and reporting. Evaluation of instructor performance at UPT BPP Sukaraja is carried out every three months and six months. So far, the evaluation is done manually, so it does not need to be done in a timely manner because of constrained inadequate labor. The method used in the evaluation study is the use of agricultural instructors using the Bayes method. The Bayes method is first performed by calculating the value of each criterion, total weighting, probability perriterian, calculating the total probability, calculating the threshold of each criterion and calculating the threshold value then comparing the total value with the threshold value of each criterion. The results of this method produce a good agriculture instructor ranking ranking, namely with initial Sdn with a total value of probability 31.38 and those requiring guidance are extension agents with Sjn and Dsm with a total probability of 24.13, and a total probability of 24.